2021
DOI: 10.2166/ws.2021.304
|View full text |Cite
|
Sign up to set email alerts
|

Using data mining methods to improve discharge coefficient prediction in Piano Key and Labyrinth weirs

Abstract: As a remarkable parameter, the discharge coefficient (Cd) plays an important role in determining weirs' passing capacity. In this research work, the SVM and the GEP algorithms were assessed to predict Cd of piano key weir (PKW), rectangular labyrinth weir (RLW), and trapezoidal labyrinth weir (TLW) with gathered experimental data set. Using dimensional analysis, various combinations of hydraulic and geometric non-dimensional parameters were extracted to perform simulation. The superior model for the SVM and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…For this purpose, SVM (support vector machines) and the GEP (gene expression programming) models were used. They reported that the GEP model results are in a good agreement with the experimental data [23]. In another study, the discharge coefficient of oblique sluice gates was assessed using some different techniques and the ANN (artificial neural network) approach was introduced as the most accurate model [24].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…For this purpose, SVM (support vector machines) and the GEP (gene expression programming) models were used. They reported that the GEP model results are in a good agreement with the experimental data [23]. In another study, the discharge coefficient of oblique sluice gates was assessed using some different techniques and the ANN (artificial neural network) approach was introduced as the most accurate model [24].…”
Section: Introductionmentioning
confidence: 78%
“…The Correlation Coefficient (CC), Root Mean Square Error (RMSE), Willmott's Index (WI), Legates and McCabe's Index (LMI), Mean Absolute Error (MAE), efficiency of the Nash Sutcliffe model (NS), Normalized Root Mean Square Error (NRMSE), and Root Mean Square Relative Error (RMSRE) were used for assessing the training and testing phases of prediction models [40][41][42][43][44][45][46][47][48][49]. It is possible to quantify the six performance assessment parameters used in this research using Equations ( 17)- (23).…”
Section: Parameters For Performance Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the flow pattern is turbulent or the flow pattern is rapidly changing, the individual probe will not be able to accurately obtain the path flow velocity, and the flow velocity area method will produce large errors when used for flow calculation. Due to the lack of a professional platform for the detection and testing of measurement and control gates, few studies have been carried out to investigate the calibration method for flow in the measurement box of the measurement and control gate [22,23]. It is very important to calibrate the accuracy of the path flow velocity measured by the probe inside the measurement box during the development and debugging process of the measurement and control gate.…”
Section: Discussionmentioning
confidence: 99%
“…In the initial set of experiments, two unprotected abutments were tested, and it was observed that the highest scour depth occurred at the abutment toe. Therefore, the abutments toe was chosen as the reference point for comparison of the scouring in all subsequent experiments, as it was in similar studies [28,46,47]. The topography around the abutment was recorded in a 2 × 2 cm grid using a laser distance meter that could move in longitudinal and cross-sectional directions with 1 mm accuracy.…”
Section: Methodsmentioning
confidence: 99%